Efektivitas kebijakan penggunaan sirekap untuk transparansi rekapitulasi pada rapat pleno Kabupaten Tebo pemilu 2024 - Nasuhaidi, Nasuhaidi; Ahmad, Zakly Hanafi; Rahmadhani, Suci; Asiah, Uswatun (Proceedings Academic Universitas Jambi, 2025)
The 2024 General Election represents a significant step toward strengthening democratic transparency in Indonesia through the use of information technology. A key innovation is the General Elections Commission (KPU)'s adoption of the Recapitulation Information System (SIREKAP), designed to digitally recapitulate vote counts at the Polling Station (TPS) level in near real time. This study examines the effectiveness of the SIREKAP policy in enhancing transparency, implementing a tiered correction mechanism, and ensuring accountability in the recapitulation process in Tebo Regency, Jambi Province. Employing a qualitative descriptive approach with a case study design, data were collected through in-depth interviews, document analysis, and cross-verification of plenary correction practices. The findings reveal that SIREKAP functioned as an early warning system capable of detecting anomalies, such as discrepancies of several thousand votes in the districts of Tengah Ilir and Sumay. Tiered corrections based on digital evidence (C-Hasil) result photos, timestamps, and upload logs strengthened the legitimacy of plenary sessions and produced decisions that were broadly accepted by stakeholders. Furthermore, manipulations initially detected through SIREKAP led to both ethical and criminal sanctions against perpetrators, demonstrating a comprehensive chain of accountability. However, the effectiveness of SIREKAP remains conditional, as vulnerabilities persist in manual data entry and undocumented corrections. In conclusion, SIREKAP's role in strengthening electoral transparency and accountability can only be fully optimized when supported by participatory oversight, a clear audit trail system, and the independence of supervisory institutions.